2007
DOI: 10.1007/s00418-007-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human placental antigen complex X-P2 (hPAX-P2) anti-serum recognizes C-terminus of huntingtin-associated protein 1A common to 1B as a determinant marker for the stigmoid body

Abstract: The anti-serum against an unknown human placental antigen complex X-P2 (hPAX-P2) immunohistochemically recognizes three putative molecules (hPAX-P2S, hPAX-P2N, and hPAX-P2R), each of which is associated with the stigmoid bodies (STBs), necklace olfactory glomeruli (NOGs), or reticulo-filamentous structures (RFs) in the rat brain. The STBs also contain huntingtin-associated protein 1 (HAP1), and the HAP1-cDNA transfection induces STB-like inclusions in cultured cells. In order to clarify the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The stigmoid bodies (STBs) are spherical-to-ovoidal, nonmembrane-bound neurocytoplasmic inclusions (0.5-3 m in diameter) containing human placental antigen complex X-P2S (hPAX-P2S) in the rat brain (Shinoda et al 1992(Shinoda et al , 1993Nagano and Shinoda 1994;Fujinaga et al 2007). We recently showed that hPAX-P2S is identical to huntingtinassociated protein 1 (HAP1) ), indicating that HAP1-immunoreactive inclusions previously reported in rodent brains (Gutekunst et al 1998;Li et al 1998aLi et al , 2003Sheng et al 2006) correspond to the STB containing the hPAX-P2S (Shinoda et al 1993).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The stigmoid bodies (STBs) are spherical-to-ovoidal, nonmembrane-bound neurocytoplasmic inclusions (0.5-3 m in diameter) containing human placental antigen complex X-P2S (hPAX-P2S) in the rat brain (Shinoda et al 1992(Shinoda et al , 1993Nagano and Shinoda 1994;Fujinaga et al 2007). We recently showed that hPAX-P2S is identical to huntingtinassociated protein 1 (HAP1) ), indicating that HAP1-immunoreactive inclusions previously reported in rodent brains (Gutekunst et al 1998;Li et al 1998aLi et al , 2003Sheng et al 2006) correspond to the STB containing the hPAX-P2S (Shinoda et al 1993).…”
Section: Introductionmentioning
confidence: 88%
“…We recently showed that hPAX-P2S is identical to huntingtinassociated protein 1 (HAP1) ), indicating that HAP1-immunoreactive inclusions previously reported in rodent brains (Gutekunst et al 1998;Li et al 1998aLi et al , 2003Sheng et al 2006) correspond to the STB containing the hPAX-P2S (Shinoda et al 1993). In addition, transfection of HAP1-cDNA into HEK293 cells leads to the formation of STBs determined by both conventional and immuno-electron microscopy (Li et al 1998a;Fujinaga et al 2007). Therefore, HAP1 is considered to be a determinant marker of STB and transfection of its gene into cells provides an in vitro model of STB formation.…”
Section: Introductionmentioning
confidence: 96%
“…The SBs are structures found in the cytoplasm of various types of neurons in the central and peripheral nervous system. [94][95][96] They are distinct, spherical-to-ovoidal and non-membrane-bound neuronal cytoplasmic inclusions (~0.5-3 渭m in diameter) with a granulo-fuzzy texture and moderate-to-low electron density, 97 and are found abundantly in the preoptic, hypothalamic and limbic 473 and 582) both bind the conserved C-terminal TBP domain. 74 When HAP1 or TBP were expressed independently in COS-7, 293, or Neuro-2a cells, all TBP localizes to the nucleus and all HAP1 assembles into cytoplasmic stigmoid-like bodies (STLBs).…”
Section: Hap1 May Play a Role In The Generation Of Inclusion Bodiesmentioning
confidence: 99%
“…11,15 SBs containing HAP1 also are found to contain the unknown human placental antigen complex X-P2 (hPAX-P2) and apolipoprotein E receptor, SorLA/LR11 and sortilin (two members of the vacuolar protein sorting 10 (VPS10) domaincontaining family). [94][95][96] HAP1 is a core component of the SBs and important for fetal and early postnatal neural development, particularly in the hypothalamic or limbic networks and HAP1/SBs has been assumed to play a protective role against neurodegeneration in HD. 96,99 Whether HAP1 plays any role in the pathological protein aggregation such as in Alzheimer disease, Parkinson disease and Huntington disease is not clear.…”
Section: Hap1 Regulates Recycling Of Membrane Receptors and Is Involvmentioning
confidence: 99%
See 1 more Smart Citation